Coulomb-Dominated Oscillations in Fabry-Perot Quantum Hall Interferometers - 朱玉莹 白孟孟 郑树玉 樊洁 景秀年 姬忠庆 杨昌黎 刘广同 吕力 (Chinese physics letters, 2017)
Periodic resistance oscillations in Fabry-Perot quantum Hall interferometers are observed at integer filling factors of the constrictions, fc=1, 2, 3, 4, 5 and 6. Rather than the Aharonov-Bohm interference, these oscillations are attributed to the Coulomb interactions between interfering edge states and localized states in the central island of an interferometer, as confirmed by the observation of a positive slope for the lines of constant oscillation phase in the image plot of resistance in the 13 Vs plane. Similar resistance oscillations are also observed when the area A of the center regime and the backseattering probability of interfering edge states are varied, by changing the side-gate voltages and the configuration of the quantum point contacts, respectively. The oscillation amplitudes decay exponentially with temperature in the ramge of 40mK〈 T ≤ 130 mK, with a characteristic temperature T0 -25 mK, consistent with recent theoretical and experimental works.